Numerical investigation on fire resistance of superior high performance steel column under axial compression - Zenha, K. Fathimath; Rajeevan, B. (Journal of Structural Engineering, 2024)
Superior high-performance steel is an advanced type of steel. Columns are the critical members of a structure. Columnssubjected to fire may fail due to overall buckling, flange buckling, or member instability. This study concentrates on the overall buckling failure of superior high-performance steel columns under axial compression subjected to fire. The critical temperature and amount of axial elongation of columns when subjected to firewere analysed in detail. The critical temperature and axial elongation of columns are affected by their geometrical parameters. The present study carried out a numerical investigation using finite element software ANSYS®. The existing experimental results in the literature were used to develop the numerical models, which were validated against the results obtained from experiments. After successful validation, a detailed parametric study was conducted. Mainly six sets of parameters were considered in this study, which are related to flange slenderness ratio, web slenderness ratio, size of perforations, spacing of perforations, spacing of stiffeners, and cross-sectional shape. The influence of axial load ratio on the effect of geometric parameters was also studied. The specimen showed an 11°C increasein critical temperature without affecting the pre-failure behaviour when the web depth to web thickness ratio was increased from 3 to 9. The increase in flange width to flange thickness ratio from 3 to 9 under an axial load ratio of 0.7 increased the axial elongation by about 10 mm in addition to a 20% increase in the critical temperature. Columns with closely spaced and larger perforations failed at an early temperature without affecting the amount of axial elongation.